(3OQGSGJ aj GdeMGSHI GdeGdjI hGdJcGdja hGdeMGSHI GdEOGQjI (B/s - (3YWjI, gGTe CMeOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI ddfTQ(B, s, 2000)
(3GdeMGSHI GdeGdjI(B- (3GdeMGSHI GdEOGQjI heMGSHI GdJcGdjas
Keywords: (3GdEOGQIs; (3GdeMGSHI GdeGdjIs